An introduction to object-oriented analysis - Brown, David William (Wiley, 2002)
This book is a very general and accessible introduction to Object Oriented Analysis. It contains extensive pedagogy and incorporates patient explanations, making it ideal for beginners. Incorporation of real-world examples, case studies, and in depth theory and skills for practical application makes this book very user-friendly.